A study of pattern of pathogen and their sensitivity isolated from surgical site infections in abdominal surgeries - M. S., Anilkumar; K. R., Deepakraj (International Surgery Journal, 2019)
Background: Surgical site infection (SSI) is defined as those infections presenting up to 30 days after a surgical procedure if no prosthetic is placed and up to 1 year if prosthesis is implanted in the patient. SSI contributes to increasing morbidity, mortality and cost related to surgeries and continues to be a major problem even in tertiary care modern hospitals following standard protocols of peri operative preparation and antibiotics prophylaxis. Objective of this study was to study and analyse the pattern of pathogen causing SSI in abdominal surgeries in a tertiary care hospital. Methods: Descriptive study on patients undergoing abdominal surgery in the department of surgery. Patients satisfying inclusion criteria will be assessed on 2nd postoperative day and then daily for surgical site pain, redness, warmth, discharge and swelling of surgical site till the patient gets discharged and followed up after discharge every 7 days up to 1 month. If SSI is detected, swab will be taken and sent for culture and sensitivity. Results: At the end of the study, after analysing the pattern of pathogens and antibiotic susceptibility, we intend to conclude the safe usage of empirical antibiotic prophylaxis to prevent the incidence of SSI’s in our hospital. Conclusions: Appropriate prophylactic therapy for any open abdomen surgeries reduces incidence of surgical site infection thereby reducing morbidity, mortality and cost burden in patients undergoing abdominal surgeries.